Taiwan’s National Health Insurance Research Database: administrative health care database as study object in bibliometrics - Chen, Yu-Chun; Yeh, Hsiao-Yun; Wu, Jau-Ching; Haschler, Ingo; Chen, Tzeng-Ji; Wetter, Thomas (Scientometrics, 2011)
The trend to use administrative health care databases as research material is increasing but not well explored. Taiwan’s National Health Insurance Research Database (NHIRD), one of the largest administrative health care databases around the world, has been used widely in academic studies. This study analyzed 383 NHIRD studies published between 2000 and 2009 to quantify the effects on overall growth, scholar response, and spread of the study fields. The NHIRD studies expanded rapidly in both quantity and quality since the first study was published in 2000. Researchers usually collaborated to share knowledge, which was crucial to process the NHIRD data. However, once the fundamental problem had been overcome, success to get published became more reproducible. NHIRD studies were also published diversely in a growing number of journals. Both general health and clinical science studies benefited from NHIRD. In conclusion, this new research material widely promotes scientific production in a greater magnitude. The experience of Taiwan’s NHIRD should encourage national- or institutional-level data holders to consider re-using their administrative databases for academic purposes.